Intermediate Accounting : Financial Accounting (Part One) - Simons, Harry (Mandaluyong City, Philippines : Mutual Books, Inc., 1977)
Recognizing the need for more detailed and comprehensive books that are adapted for use in the Philippines, the mutual books, inc., licensee of South-Western Publishing company, commissioned the undersigned to prepare the Philippine edition of Intermediate accounting by Harry Simons.
Chapter 1. basic accounting concepts and principles -- 2. Financial statements -- 3. Cash and temporary investments -- 4. Receivables -- 5. Inventories - cost procedures -- 6. Inventories - special valuation procedures -- 7. Inventories - estimating procedures in valuation -- 8. Investments - stock -- 9. Investments - bonds, funds, and miscellaneous -- 10. Land, buildings, and equipment - acquisition, use, and retirement -- 11. Land, buildings, and equipment - depreciation and depletion -- 12. Land, buildings, and equipment - revaluation -- 13. Tangible assets -- 14. Current and contigent liabilities -- 15. Long-term liabilities -- 16. Paid-in capital upon corporate formation -- 17. Paid-in capital - changes subsequent to corporate formation -- 18. Retained earnings - earning and earnings distribution.
Includes index.
Keywords: ACCOUNTING